Different Teaching Approaches for Vocal Projection in Classical Singing (Per Musi, 2018)
There are different views about how to develop vocal projection in classical singing, although this feature is routinely emphasized in the practice of this style of singing. The objective of this research was to analyze different teaching approaches of vocal projection in classical singing, from the perspective of teachers who work in this area. According to the participants, the five aspects that involve body, breath, perception/proprioception, use of images in teaching and production of the voice can base the development of effective vocal projection in classical singing.